Innovation in Islamic Banking Services for Sustainable Development: An Analysis of the Alignment of Islamic Values with SDGs - Mardelia Desfrida; Amrin; Obydur Rahman (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to analyse the alignment of Islamic banking service innovations with the Sustainable Development Goals (SDGs) through a maqāṣid al-sharī‘ah–based values approach, positioning Islamic finance as a strategic actor in sustainable development. Theoretical framework: Integrates maqāṣid al-sharī‘ah principles, particularly justice (‘adl), public benefit (maṣlaḥah), and balance (tawāzun), with the multidimensional SDG paradigm encompassing economic growth, social equity, and environmental sustainability. Literature review: Conceptualisation of service innovation in Islamic banking, the relationship between Sharia values and the Sustainable Development Goals, and integration of innovation and sustainability in Islamic banking practices. Method: Employing a qualitative research design based on library research, data were analysed through stages of presentation, conceptual development, and conclusion drawing, using a hermeneutic approach to interpret the substantive relationships between maqāṣid principles and SDG targets. Results: the findings reveal a strong conceptual convergence between Islamic ethical values and key SDG dimensions, particularly poverty alleviation, social equality, and environmental protection, leading to the formulation of the Shariah Sustainable Service Framework (SSSF), which comprises three interconnected pillars: spirituality as a moral foundation, social justice as the orientation of benefit distribution, and economic efficiency as an instrument of productive sustainability. Implications: This framework provides normative and strategic guidance for Islamic financial institutions in designing ethically grounded and sustainability-oriented service innovations, while offering regulators and policymakers a reference for strengthening sharia-based governance aligned with global development agendas. Novelty: This study lies in the development of an original integrative framework that systematically bridges maqāṣid al-sharī‘ah values with SDG indicators, advancing Islamic banking from a compliance-driven model toward a value-based paradigm of sustainable development.